Das Warten auf – Geschichte und Funktionswandel eines literarischen Topos von Solveigs Lied bis Hjalmar Bergmans Herr von Hancken - Brynhildsvoll, Knut (Folia Scandinavica Posnaniensia, 2007)
My contribution deals with the changing aspects of the situation of "Waiting for ..." as a literary topie in the Scandinavian literaturę from Ibsen's "Peer Gynt" to Hjalmar Bergmans novel "Herr von Hancken" - with a subseąent outlook on the reuse of the motif in the time between the two world wars. The analysis of important works of Scandinavian Hterature during this period - including works of Ibsen, Strindberg, Lagerlof, Hj. Bergman, H. Aanrud - shows very clearly that the main characters as a conseąuence of the loss of the intended or expected object are inclined to transform their reality and thus replace the empty position of the object with the most phantastic projections of a secondary, artificiel world which has no similarity with the empirical world of common experience. On the contrary. Due to the subjecfs free disposal over the object-area it is possible for them to create a fictional world which approaches the world of madness and in which the authors are expressing the crisis and the solitude of human beeing under the conditions of modem society.